Effect of stirring time on the structural parameters of nanophotonic LiNbO 3 deposited by spin-coating technique - Al-Douri, Yarub; Fakhri, Makram A.; Badi, Nacer; Voon, Chun Hong (Elsevier, 2018)
Lithium niobate (LiNbO3) photonic crystals are deposited on quartz substrate by using spin coating technique. The mixture is prepared with different stirring time (8 h, 24 h, 48 h). The LiNbO3 nanostructures are analyzed by X-ray diffraction. The results show that as mixing time increases, the XRD starts to become structurallymore regular and high crystallization, therefroe it is found that the best mixing time was 48 h related to ideal syntheiss. The effect of different annealing temperatures (400, 500, and 600 °C) on the structural properties is elaborated studied towards finding ideal conditions for the preparation of optical waveguides.